Бондарихинская и чернолеская культуры: проблема взаимосвязей (по материалам городища у с. Веселое на Харьковщине) - Буйнов, Ю. В. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryJ. Buinov. Bondariha and Chernolesskaya Cultures: a Problem of Interrelation (on the Materials of Bilfort Near the Village Veseloye in Kharkov Region)A materials of hilfort near the village Veseloye in Kharkov region allow to date this monument IX–VIII centuries B.C. In all details they coincide with settlement near the village Huhri on the Vorskla. This fact denies a hypothesis of some scholars about resettlement of a part of tribes Chernolesskaya cultura to the left bank of Dnieper and replacement by them of carriers of Bondariha cultura.